Evaluation of Costumer Attitudes: Attributes Product of Mango Peel Powder - Fadilah, Arsy Nur (Universitas Wiralodra, 2024)
Indramayu is the number one mango fruit producing city in West Java Province. While there has been no handling and processing of home industrial waste. This can cause serious problems in the environment. There is a need for an economic and environmentally based waste management system. One of them solution is processing mango peel waste into GOPE (mango peel) powder, products as a natural food additive to replace essence powder products and synthetic powder for food and drinks. The purpose of this study is to analyze consumer attitudes towards the mango peel powder. Consumer attitude is an emotional expression of consumers that shows whether consumers like an object or not so that attitudes can describe the level of consumer confidence in products or services. Consumer attitudes on mango peel powder product attributes describe what priority attributes are taken into consideration in choosing product. This research is a quantitative descriptive using Fishbein's multi-attribute method. Fishbein's Multiattribute Model can measure consumer attitudes using three components: the level of importance, trust, and attitude evaluation. There are thirty who are consumers have consumed essence powder products in the last two months and selected using accidental sampling . The results of this study indicate that research respondents have a positive attitude towards five attributes of Taste, texture, form, composition, smell and one of them are netral about one attributes: colour.